Sustainable Intensification and Climate-Smart Yam Production for Improved Food Security in West Africa: A Review - Owusu Danquah, Eric; Danquah, Frank Osei; Frimpong, Felix; Dankwa, Kwame Obeng; Weebadde, Cholani Kumari; Ennin, Stella Ama; Asante, Mary Otiwaa Osei; Brempong, Mavis Badu; Dwamena, Harriet Achiaa; Addo-Danso, Abigail; Nyamekye, Daniel Rexford; Akom, Mavis; et al. (Frontiers in Agronomy, 2022)
Intensification of staple food crops such as Yam (Dioscorea spp.), whiles sustaining the environment, is imperative in providing food for the expected 9.6 billion global population by 2050. In West Africa (WA), amidst the threat posed by climate change on food security, yam production is associated with deforestation and land degradation. Integrated soil fertility management (ISFM) and improved staking options for intensification and sustainable yam production on continuously cropped fields hold the key to addressing this challenge. This paper evaluates the last decade yam production trends in WA and three leading yam-producing countries of Nigeria, Ghana, and Côte d’Ivoire using FAOSTAT data. A production increase of 1.72, 1.43, and 1.35 times resulted in an area harvest increase of 2.25, 1.23, and 1.59 times for Nigeria, Ghana, and Côte d’Ivoire, respectively. Nigeria and Côte d’Ivoire had the worse yam productivity across the decade by producing at an average yield of 17.3% and 12.5% respectively of the estimated potential yam yield (50 t ha-1). Even in Ghana, where productivity increased across the decade, average productivity was 33% of the estimated potential yield. Thus, it can be observed that the primary reason for the increase in yam production across the globe and WA is mainly because of the increase in area under cultivation in the major yam-producing countries. Climate change projects future erratic rainfall and elevated daily mean temperature to cause declining tuber yields. Meanwhile, the importation of food such as rice as a strategy to improve food availability cannot be accessed by poor rural households due to the strong correlation between international food price hikes and prices of these foods. However, there is less relationship between international yam price hikes and yam prices in West Africa. Therefore, yam production and sustenance could be vital for food security for the increasing population WA. This paper reviews current research on soil fertility and staking options for sustaining yam production on continuously cropped fields. Promotion and adoption of these improved technologies would enhance food security and contribute to achieving S.D.G.s 1 (No poverty), 2 (Zero hunger), 13 (Climate action), and 15 (life on land).